Thrombocyte decrease and hemoglobin level as simple non-inflammatory predictors of anastomotic leakage in rectal-cancer surger - Řezáč, Tomáš; Vrba, Radek; Klos, Dušan; Zbořil, Pavel; Špička, Petr; Klementa, Ivo; Starý, Lubomír (Bratislavské lekárske listy, 2023)
PURPOSE: The study aimed to determine a simple diagnostic test that could predict the risk of anastomotic leakage in early postoperative period. METHODS: A single-center, retrospective study was conducted. The electronic medical records of patients who underwent resection for rectal tumor between January 1, 2016, and December 31, 2021, in University Hospital Olomouc, were reviewed. The data included risk factors for leakage and laboratory parameters commonly obtained. RESULTS: The decrease in platelets was significant as for the possibility of being a marker of anastomotic leakage; OR = 0.980 (p = 0.036). A decrease of 34 or higher predicts leakage with a sensitivity of 45 % (95 % CI: 23.1–68.5 %) and specificity of 81.1 % (95 % CI: 75.2–86.1 %). Postoperative leukocyte blood level (OR = 1.134; p = 0.019) and leukocyte level on postoperative day 1 (OR = 1.184; p = 0.023) were significant predictors for leakage. WBC values ≥ 8.8 predict leakage with a sensitivity of 70.0 % (95 % CI: 45.7–88.1 %) and specificity of 55.3 % (95 % CI: 48.4–62.0 %). Hemoglobin blood level ≤ 79.5 predicts leakage with a sensitivity of 70.0 % (95 % CI: 45.7–88.1 %) and specificity of 62.2 % (95 % CI: 55.5–68.7 %). CONCLUSION: Despite the fact that the specificity and sensitivity of the followed parameters are low, they could serve as markers useful for early diagnosis or suspicion for leakage (Tab. 5, Fig. 3, Ref. 14).